Peer supporter experiences of home visits for people with HIV infection - Lee HJ (Dove Medical Press, 2015)
Han Ju Lee,1 Linda Moneyham,2 Hee Sun Kang,3 Kyung Sun Kim41Department of Nursing, Sangmyung University, Cheonan-si, Chungcheongnam-do, South Korea; 2School of Nursing, University of Alabama at Birmingham, Birmingham, AL, USA; 3Red Cross College of Nursing, Chung-Ang University, Seoul, South Korea; 4Gyeonggi Branch, Korean Alliance to Defeat AIDS, Anyang, Gyeonggi-do, South KoreaPurpose: This study's purpose was to explore the experiences of peer supporters regarding their work in a home visit program for people with HIV infection.Patients and methods: A qualitative descriptive study was conducted using focus groups. Participants were 12 HIV-positive peer supporters conducting home visits with people living with HIV/AIDS in South Korea. Thematic analysis was used to analyze the data.Results: Six major themes emerged: feeling a sense of belonging; concern about financial support; facing HIV-related stigma and fear of disclosure; reaching out and acting as a bridge of hope; feeling burnout; and need for quality education. The study findings indicate that although peer supporters experience several positive aspects in the role, such as feelings of belonging, they also experience issues that make it difficult to be successful in the role, including the position's instability, work-related stress, and concerns about the quality of their continuing education.Conclusion: The findings suggest that to maintain a stable and effective peer supporter program, such positions require financial support, training in how to prevent and manage stress associated with the role, and a well-developed program of education and training.Keywords: human immunodeficiency virus, qualitative research, workplace experience